Peran Dan Struktur Labai Dalam Sosial Keagamaan Di Kesultanan Sambas Kalimantan Barat 1913-1943 M - Lupiana; Beti Yanuari Posha (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2025)
This study examines the role and status of Labai in the social and religious structure of the Sambas Sultanate, West Kalimantan 1913-1943 M. The main focus of this study is how Labai's position as a village religious official has a significant contribution to the implementation and supervision of the religious life of the local community, especially after the appointment of Muhammad Basiuni Imran as Maharaja Imam in 1913. This study uses a historical research method that includes the stages of heuristics, verification, interpretation, and historiography. The findings of this study indicate that Labai not only played a role as a prayer leader, a teacher of the Koran, and an implementer of the fardhu kifayah ritual, but also became a manager of zakat and a central figure in the moral and religious development of the village community. The strict selection process by the Maharaja Imam emphasized the importance of scientific competence and integrity in the appointment of Labai. Although in the contemporary context the religious function at the village level has been taken over by religious instructors under the Ministry of Religion, the existence of Labai during the Sambas Sultanate had a strategic role in shaping the Islamic identity of the community and maintaining social stability based on religious values.